Utilizing organic amendments for general suppression of dollar spot on creeping bentgrass turf. Issue 1 (16th April 2021) - Beckley, Cody James; Roberts, Joseph Anthony
Abstract: Dollar spot ( Clarireedia spp.) negatively impacts the aesthetic value and playability of golf course fairways. A 2‐yr field trial was conducted to examine organic amendment effect on dollar spot severity and on fungicide residual efficacy for dollar spot control on creeping bentgrass ( Agrostis stolonifera L. '007'). Treatments were arranged in a 7 × 5 split‐plot factorial measuring the effect of fertilizer source (soil incorporated organic biosolids compost, soil incorporated biochar, surface applied organic biosolids compost, surface applied biochar, vermicompost extract, standard fertilizer, or non‐treated) on control of dollar spot by five fungicide treatments (fluazinam 14 d, fluxapyroxad 14 d, fluazinam threshold, fluxapyroxad threshold, none) applied at product label rates. Nitrogen fertility levels for all treatments were standardized at ∼205 kg N ha –1 annually. Threshold fungicide treatments were applied when three or more infection centers per area were counted on two or more of four trial replicates. In 2017, all fertilizer treatments were significantly more effective at reducing disease than non‐treated, but were statistically similar. In 2018, biochar, vermicompost, and standard fertilizer treatments were significantly more effective than organic biosolids compost and non‐treated. Fungicides controlled dollar spot when applied every 14 d. In 2017, all fertilizer treatments reduced the number of threshold sprays compared to none, yet the same effects were not consistently observed in 2018. Study results illustrate the effectiveness of nitrogen application for mitigating dollar spot disease on creeping bentgrass during establishment compared to no fertilizer, potentially allowing for reduced fungicide use to control the disease. Core Ideas: Dollar spot is a devastating disease of turfgrass. Successive fungicide applications are often required in close cut turf. Organic amendments supply plant available N to reduce dollar spot. Adequate N fertility can reduce fungicide applications needed to control dollar spot.